Implementasi Good Governance di Kecamatan Sabangau Kota Palangka Raya - Muhamad Yusuf (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
In the authors use a qualitative approach. According to Sugiyono (2011:8)